E-learning one step in gaining knowledge - Alawi, Sittie Rahma V. (University of the Philippines Diliman, 2010)
Account x of Sykes Asia implements a learning process called "Closed Loop", this focuses on the learning challenges our front liners encounter. These challenges affects directly their performance, thus, affects the account's KPIs. The Close Loop process resolves on identifying first the data source or what specific KPI are we focusing on; then identifies the challenged front liners. Understand and identify the root cause of the performance opportunities and most often, it's about learning gaps. And as part of Sykes Asia services, the company aims to continue satisfy their clients' needs through providing excellent customer service to their customers. Thus, as part of this mission, this project proposed a new method to address the learning gaps of Account X and to continue meeting up the client's expected performance out of our front liners. The proposed E-leaning system facilitates the setup of a centralized and accessible E-Learning, containing all training materials and best known methods of the account. The project aims to optimize time allotted for training and to properly channel the needed training modules for specific learning needs of our front liners